Color perception of the observer with the manifestation of the chromatic effect of crispening - Hajdek, Krunoslav (Array, 2018)
This research presents the results of the appearance of chromatic effect of crispening on a designer solution in which the primary stimuli are made in the purple color with the values of 55% RTV and 65% RTV and backgrounds are made in the green-blue color, and their variations are designed in the values of 25% RTV, 50% RTV, 75% RTV and 100% RTV that are placed around the primary stimuli. The test subjects (n=10) that took part in the research had the task to equalize the test primary stimuli with the referential stimuli on a computer screen with the help of the technique of simultaneous binocular harmonization. The strength of the crispening effect was defined and shown in the CIEDE00 system. The conclusion of the conducted tests indicates that the intensity of crispening was stronger on the test primary stimuli 65% RTV, where the differences in the perception of color were more significant.